Enhanced Voltammetric Sensing Platform Based on Gold Nanorods and Electrochemically Reduced Graphene Oxide for As(Iii) Determination in Seafood Samples - Aguirre-Quintana, M; Aguirre-Quintana, M; Segura-Segura, R; Segura-Segura, R; Pizarro-Reyes, J; Pizarro-Reyes, J; Flores-Vergara, E; Flores-Vergara, E (Springer Science and Business Media B.V., 2024)
A glassy carbon electrode (GCE) modified with electrochemically reduced graphene oxide (ErGO) and gold nanorods (AuNRs) (GCE/ErGO/AuNRs) was prepared for determining As(III) in bivalve mollusks samples (Mytilus chilensis). The modified electrode was characterized by cyclic voltammetry, scanning electron microscopy (SEM), and atomic force microscopy (AFM). Chemical and electrochemical parameters were optimized, observing that the presence of AuNRs provides selectivity, while the incorporation of ErGO improves the sensitivity of the modified electrode for the detection of As(III). Using square wave anodic stripping voltammetry (SWASV), a linear range of 2.0–60.0 µg L−1 with a detection limit (LOD) of 0.21 µg L−1 was obtained. The validation was made using water and mussel tissue-certified reference materials (TMDA-64.2 and ERM®-CE278k, respectively), showing good accuracy and reproducibility. The methodology allowed the determination of As(III) in real samples of marine resources, with excellent results (RSD < 2%). Graphical abstract: (Figure presented.). © The Author(s), under exclusive licence to Springer Nature B.V. 2023.